Comparison between ticagrelor and clopidogrel in high bleeding risk patients with acute coronary syndrome. (3rd October 2022) - Tjerkaski, J; Jernberg, T; Alfredsson, J; Erlinge, D; James, S; Lindahl, B; Mohammad, M A; Omerovic, E; Venetsanos, D; Szummer, K
Abstract: Background: Potent antiplatelet agents such as ticagrelor are associated with a lower risk of ischemic events than clopidogrel in patients with acute coronary syndrome (ACS). However, it is uncertain whether the benefits of more intensive anti-ischemic therapy outweigh the risks of major bleeding in individuals who have a high bleeding risk (HBR). This study aimed to assess treatment outcomes following dual antiplatelet therapy (DAPT) using either ticagrelor or clopidogrel in ACS patients with HBR. Methods: All HBR patients enrolled in the SWEDEHEART registry who were discharged with DAPT using ticagrelor or clopidogrel following ACS between 2010 and 2017 were included in this study. Bleeding risk was assessed using the 4-item PRECISE-DAPT score, which consists of age, prior bleeding, haemoglobin concentration and creatinine clearance. HBR was defined as a PRECISE-DAPT score ≥25. Inverse-probability of treatment weighting was used to adjust for baseline differences between the treatment groups. The main analysis consisted of a doubly robust estimation of causal effect using Cox proportional hazards models. Data on major bleeding, recurrent myocardial infarction (MI), ischemic stroke and all-cause mortality was obtained from national registries, with 365 days of follow-up. Additional outcomes include major adverse cardiovascular events (MACE), a composite of MI, ischemic stroke and all-cause mortality, and net adverse clinical events (NACE), a composite of MACE and major bleeding. Results: Of all ACS patients, 36% (n=25, 042) had a PRECISE-DAPT score ≥25. Approximately half of the study participants were treated with ticagrelor (n=11, 848). Ticagrelor reduced the risk of MI (hazard ratio [HR], 0.82 [95% CI 0.74–0.91]), ischemic stroke (HR, 0.73 [95% CI 0.60–0.88]) and MACE (HR, 0.90 [95% CI 0.84–0.97]), while also increasing the risk of major bleeding compared to clopidogrel (HR, 1.30 [95% CI 1.16–1.47]). We found no significant differences in all-cause mortality (HR 1.02 [95% CI 0.92–1.12]) and NACE (HR 0.98 [95% CI 0.92–1.05]). Conclusions: Ticagrelor was associated with a lower risk of recurrent ischemic events, but a higher risk of major bleeding compared to clopidogrel. There were no significant differences in all-cause mortality and NACE between the treatment groups. These results suggest that more potent antiplatelet agents might not be superior to clopidogrel in ACS patients with HBR. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Stockholm county council